Penyuluhan Budidaya Perikanan Ramah Lingkungan Pendekatan Eco Engineering Di Kabupaten Konawe Utara - Mangurana, Inti; Hamzah, Muhaimin; Muh. Arsal, La Ode; Annisa Aryanti, Chairun; Imam Wahyudi, Adi; Isanayanti, Isanayanti (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
The purpose of this outreach activity is to serve the community by enhancing the knowledge and skills of household-scale fish farmers. This program is designed to provide practical guidance on managing fish farming businesses using simple household equipment, covering aspects such as seed selection, pond management, and marketing strategies for harvested products. Through a series of training sessions and educational materials, participants are expected to optimize the potential of aquaculture in Tanjung Bunga Village, Wawolesea District, North Konawe Regency. In addition, this activity aims to increase the economic income of local residents and make a tangible contribution to the development of local aquaculture enterprises. The expected outcomes include not only an increase in fish production but also an overall improvement in the welfare of the community in Tanjung Bunga Village. Thus, this outreach program is expected to serve as a sustainable model that brings positive impacts to the development of the fisheries sector in the region.